„Bitwa zrytualizowana” albo dlaczego niewolnicy Herulów walczyli bez tarcz? Pewien rytuał wojenny na tle analizy porównawczej - Kasperski, Robert (1981– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
This article presents a hypothesis that seeks to explain why Heruli slaves fought without shields in battle and why their main tactic was a daring front alassault. By examining accounts of wars fought by the Heruli and comparing them to those of two other groups of “naked warriors”, the author argues that the actions of Heruli warriors were highly ritualised and focused on achieving victory in battle. The article also addresses various topics related to military issues in the early Middle Ages.
p. 229-262
Summary in English.
Keywords: Heruli (Germanic people); frontal attac; war ritual; combat without protective armour; early Middle Ages; military art and science - history - Medieval, 500-1500; military art and science - history - Medieval, 500-1500 - historiography; civilization, Germanic - Middle Ages